A method for upgrading polyester depolymerization to carboxylate and borate by ionic liquid catalysis

By using a green ionic liquid catalyst to depolymerize PET methanol and using phenylboric acid to capture ethylene glycol to form a five-membered cyclic boric acid ester, the problem of difficulty in recycling ethylene glycol units in PET depolymerization is solved, and efficient resource utilization and high yield chemical production are achieved.

CN117603044BActive Publication Date: 2025-03-07ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311581834.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2025-03-07
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

In the existing PET depolymerization technology, it is difficult to effectively recover and convert ethylene glycol units into high-value chemicals, resulting in the problem of waste of resources and incomplete depolymerization.

Method used

The resulting ethylene glycol was captured by using a green ion liquid catalyst through PET methanol depolymerization reaction, and the ethylene glycol was captured by phenylboric acid or phenylboric acid anhydride, and cyclic was dehydrated and cyclized to form a five-membered cyclic borate ester.

Benefits of technology

It realizes the efficient methanol depolymerization of PET and the directional upgrading and recycling of ethylene glycol, and produces high-yield dicarboxylic acid esters and a variety of five-membered cyclic borate esters, solving the problem of waste of resources and incomplete depolymerization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004568672530000021
    Figure BDA0004568672530000021
  • Figure BDA0004568672530000041
    Figure BDA0004568672530000041
  • Figure FDA0005169132350000011
    Figure FDA0005169132350000011
Patent Text Reader

Abstract

The invention discloses a method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid, which relates to the comprehensive utilization of waste resources and the cascade utilization of raw materials. The method uses multiple types of green ionic liquid catalysts to catalyze the methanolysis reaction of PET, and then phenylboronic acid captures the generated ethylene glycol in situ, and forms different types of five-membered cyclic boric acid esters through dehydration and cyclization. The products of the method of the invention are carboxylic acid ester and different five-membered cyclic boric acid esters. The invention can be used for the depolymerization and upgrading of waste PET materials, and can also be used for other similar polyesters and polycarbonates, such as polyethylene adipate, polyethylene succinate and polypropylene carbonate, which are also suitable for the recovery strategy of the invention, and the products are corresponding boric acid ester, dimethyl succinate and dimethyl adipate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing dimethyl terephthalate and boric acid ester by depolymerizing PET with high selectivity, and relates to comprehensive utilization of waste resources and cascade utilization of raw materials. More specifically, the present invention relates to a method for depolymerizing various polyester raw materials including PET and polycarbonate with methanol, and obtaining high-yield dicarboxylic acid esters and various five-membered cyclic boric acid esters. Background Art

[0002] The chemical depolymerization of PET occurs through hydrolysis, alcoholysis, aminolysis or ammonialysis, and different nucleophilic reagents can be selected to attack the C=O bond in the polyester. However, the chemical depolymerization can be regarded as a monomer recovery strategy to a certain extent. The ethylene glycol produced simultaneously in the reaction is difficult to separate and recover due to its high boiling point and is usually abandoned. However, the ethylene glycol unit of PET also has great potential for conversion into high-value chemicals, and has been used to convert precursor materials into small molecule carboxylic acids and light olefins with higher added value. And this type of coupling reaction can promote the positive shift of the PET depolymerization reaction equilibrium, overcoming the bottleneck problem of incomplete PET depolymerization. Therefore, the innovative recycling of ethylene glycol units is an important issue that needs to be solved in the current field of PET depolymerization.

[0003] Ionic liquids are a type of excellent green catalyst that is non-volatile, thermally stable, and highly soluble. They are also designable and have been widely used in the fields of separation and catalysis. However, such catalysts have not been widely used in the coupled depolymerization pathway of PET.

[0004] Cyclic boric acid esters are important organoboron compounds. Due to their good functional group compatibility, simple preparation process of boronic acid derivatives, and low toxicity of boron byproducts, they have been widely used in the efficient construction of drugs and natural products. In addition, boric acid esters show better chemical selectivity and regioselectivity than boric acid in some metal-catalyzed cross-coupling reactions (such as Heck and Suzuki reactions). Usually, boric acid esters are obtained by reversible binding of diols and boric acids. Therefore, aromatic boronic acids can be used to capture EG components from waste PET, thereby solving the problem of ethylene glycol separation and achieving high-value conversion of ethylene glycol. This high-value recovery strategy helps to fully utilize PET waste at the molecular level. The only byproduct is water, which helps to alleviate the consumption of petroleum resources to a certain extent and improve the recycling value of PET waste. Summary of the invention

[0005] The present invention aims at the needs of depolymerization and product-oriented upgrading of PET waste plastics and the shortcomings of the prior art, and provides a method for upgrading polyester depolymerization to carboxylic acid esters and boric acid esters by catalyzing ionic liquids. Taking PET as a typical representative, the method uses green ionic liquids to catalyze the methanolysis reaction of PET, and the ethylene glycol generated is captured in situ by phenylboronic acid or phenylboronic anhydride, and different types of five-membered cyclic boric acid esters are formed through dehydration and cyclization.

[0006] The specific technical solutions adopted by the present invention are as follows:

[0007] A method for upgrading polyester depolymerization to carboxylate and borate by catalyzing ionic liquid, comprising:

[0008] S1. Put crushed polyester material, boric acid raw material, ionic liquid catalyst and methanol solvent into a reaction kettle to form a reaction system; wherein the polyester material is polyethylene terephthalate (PET), polypropylene carbonate, polyethylene adipate or polyethylene succinate; the boric acid raw material is aryl boronic acid or phenylboronic anhydride, and the aryl boronic acid is p-methylphenylboronic acid, 4-methoxyphenylboronic acid or 4-fluorophenylboronic acid; the ionic liquid catalyst is imidazole type ionic liquid [Emim][Ac] or [Bmim][Ac], and the structural formula is as follows:

[0009]

[0010] S2, placing the reactor containing the reaction system at a depolymerization temperature of 160-200° C. for 30-60 min of depolymerization reaction, and cooling to room temperature after the reaction is completed to obtain a depolymerization product containing dicarboxylic acid ester and aryl borate ester.

[0011] Preferably, in the reaction system, the added amount of the boric acid raw material is the same as the molar amount of the polyester material.

[0012] Preferably, in the reaction system, the added amount of the ionic liquid catalyst is 3 to 10 mol % of the polyester material.

[0013] Preferably, in the reaction system, the added amount of the ionic liquid catalyst is preferably 5 mol% of the polyester material.

[0014] Preferably, in the reaction system, the amount of methanol solvent added is 3-6 mL / mmol of polyester material.

[0015] Preferably, the polyester material is waste made of polyethylene terephthalate (PET).

[0016] Furthermore, the waste is in the form of PET waste bottles, PET matrix waste films, and PET colored bundling ropes.

[0017] Furthermore, the waste needs to be pre-crushed into centimeter-sized flakes, particles or powders before being added to the reactor, which can ensure the resource utilization effect of waste PET materials and obtain dimethyl terephthalate and aromatic borate (ABE) in a targeted manner with high yield.

[0018] Preferably, the ionic liquid catalyst is [Emim][Ac].

[0019] Preferably, the depolymerization temperature is 180°C.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The ionic liquid catalyst used in the present invention has the advantages of high efficiency and greenness, and can promote the methanolysis reaction of PET and the directional upgrading and recovery of ethylene glycol within 60 minutes.

[0022] (2) The methanol depolymerization strategy of waste plastic PET developed by the present invention has the advantages of short reaction time and high catalytic efficiency, and can achieve complete conversion of PET under standard reaction conditions. The strategy has a wide range of applications, and the types of waste PET raw materials are varied. Various types of waste PET materials, such as various types of PET waste bottles, PET matrix waste films, PET colored ropes and PET non-woven fabrics, can all be efficiently upgraded and converted in a short time.

[0023] (3) The PET waste plastic matrix material of the present invention can be replaced by various polyesters and polycarbonates having similar diol units, such as polyethylene succinate, polyethylene adipate and polypropylene carbonate, which to a certain extent shows the high applicability of the strategy and further broadens the scope of waste plastic treatment materials. Under the premise of ensuring high depolymerization efficiency and rapid reaction time, the corresponding conversion can be completed to obtain dicarboxylic acid esters and boric acid esters. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below through specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0025] The present invention provides a method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by ionic liquid catalysis. The method uses a green ionic liquid catalyst to catalyze the methanolysis of PET, and then phenylboronic acid captures the generated ethylene glycol in situ, and then dehydrates and cyclizes to form different types of five-membered cyclic boric acid esters. The specific steps of the method are as follows:

[0026] S1, placing crushed polyester materials, boric acid raw materials, ionic liquid catalysts and methanol solvents in a reaction kettle to form a reaction system;

[0027] S2, placing the reactor containing the reaction system at a depolymerization temperature of 160-200° C. for 30-60 min of depolymerization reaction, and cooling to room temperature after the reaction is completed to obtain a depolymerization product containing dicarboxylic acid ester and aryl borate ester.

[0028] In the subsequent examples, the raw materials in the above reaction system are as follows: the polyester material is polyethylene terephthalate (PET), polypropylene carbonate, polyethylene adipate or polyethylene succinate; the boric acid raw material is aryl boronic acid or phenylboronic anhydride, and the aryl boronic acid is p-methylphenylboronic acid, 4-methoxyphenylboronic acid or 4-fluorophenylboric acid; the ionic liquid catalyst is imidazole-type ionic liquid [Bmim][Cl], [Emim][Br], [Mmim][I], [Emim][SO3], [EMIm][BF4], [Emim][Ac] or [Bmim][Ac], and the structural formula is as follows:

[0029]

[0030] If the polyester material is PET, pure PET or PET waste can be used. The waste forms are PET waste bottles, PET matrix waste films, and PET colored ropes, but the waste must be pre-crushed into centimeter-level flakes, particles or powders before adding them to the reactor.

[0031] The following examples are used to demonstrate the reaction results under different raw materials and parameters.

[0032] Example 1

[0033] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of CR-pure PET powder (1 mmol), 0.136 grams of p-methylphenylboric acid (1 mmol), [Emim][Ac] (10 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-methylphenylboric acid ester was 87%.

[0034] Example 2

[0035] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of CR-pure PET powder (1mmol), 0.136 grams of p-methylphenylboric acid (1mmol), [Bmim][Ac] (10mol%), and 4mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as an internal standard. The results showed that the PET decomposition rate of the present embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-methylphenylboric acid ester was 84%.

[0036] Example 3

[0037] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of CR-pure PET powder (1 mmol), 0.136 grams of p-methylphenylboric acid (1 mmol), [Emim][Ac] (5 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-methylphenylboric acid ester was 91%.

[0038] Example 4

[0039] Discarded PET plastic bottles (Coca-Cola, Pepsi and Nongfu Spring brands) were crushed in centimeters in advance, and then 0.192 grams of PET plastic bottles were crushed in centimeters (1mmol), 0.136 grams of p-methylphenylboric acid (1mmol), [Emim][Ac] (5mol%) and 5mL of methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 3h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET decomposition rate of the present embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-methylphenylboric acid was 81%.

[0040] Example 5

[0041] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.152 g of 4-methoxyphenylboric acid (1 mmol), [Emim][Ac] (5 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 h. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The yield was measured by H NMR, with mesitylene as the internal standard. The results showed that the PET decomposition rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of 4-methoxyphenylboric acid ester was 87%.

[0042] Example 6

[0043] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 grams of CR-pure PET powder (1mmol), 0.139 grams of 4-fluorophenylboric acid (1mmol), [Emim][Ac] (5mol%), and 4mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1h. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as an internal standard. The results showed that the PET decomposition rate of the present embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of p-fluorophenyl borate was 94%.

[0044] Example 7

[0045] 0.102 g of polypropylene carbonate particles (1 mmol), 0.136 g of p-methylphenyl boric acid (1 mmol), [Emim][Ac] (5 mol%) and 4 mL of methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 180 ° C and reacted at this temperature for 1 h. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as an internal standard. The results showed that the decomposition rate of the polypropylene carbonate particles of the present embodiment was 100%, dimethyl carbonate and p-methylphenyl borate were produced, and the yield of p-methylphenyl borate was 92%.

[0046] Example 8

[0047] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.172 grams of polyethylene adipate (1mmol), 0.136 grams of p-methylphenylboric acid (1mmol), [Emim][Ac] (5mol%) and 4mL of methanol were added. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was warmed to 180°C and reacted at this temperature for 1h. After the reaction was completed, the temperature was cooled to room temperature, and the obtained mixed solution was the product. The obtained mixed solution was diluted with dichloromethane, and the diluent was measured by GC to determine the yield, with mesitylene as an internal standard. The result showed that the polyethylene adipate decomposition rate of the present embodiment was 100%, the dimethyl adipate yield was 98%, and the yield of p-methylphenylboric acid was 81%.

[0048] Example 9

[0049] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a program temperature controller, 0.144 gram of polyethylene succinate (1mmol), 0.136 gram of p-methylphenylboric acid (1mmol), [Emim][Ac] (5mol%) and 4mL of methanol were added. After placing the autoclave reactor, stirring and heating were opened. The reaction system was warmed up to 180 ℃, and reacted at this temperature for 1 hour. After the reaction was completed, it was cooled to room temperature, and the obtained mixed solution was the product. The obtained mixed solution was diluted with dichloromethane, and the diluent was measured by GC to determine the productive rate, and mesitylene was used as an internal standard. The result showed that the polyethylene succinate decomposition rate of the present embodiment was 100%, and the dimethyl succinate productive rate was 87%, and the productive rate of p-methylphenylboric acid ester was 86%.

[0050] Comparative Example 1

[0051] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), [Bmim][Cl] (10 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 4%, and the yield of p-methylphenylboric acid was 8%.

[0052] Comparative Example 2

[0053] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), [Emim][Br] (10 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 1%, and the yield of p-methylphenylboric acid was 4%.

[0054] Comparative Example 3

[0055] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), [Mmim][I] (10 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 2%, and the yield of p-methylphenylboric acid was 4%.

[0056] Comparative Example 4

[0057] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), [Emim][SO3] (10 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 1%, and the yield of p-methylphenylboric acid was 2%.

[0058] Comparative Example 5

[0059] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), [EMIm][BF4] (10 mol%), and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 2 hours. After the reaction was completed, the temperature was lowered to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 1%, and the yield of p-methylphenylboric acid was 2%.

[0060] The above Examples 1 to 9 and Comparative Examples 1 to 5 show that not all ionic liquids can be used to catalyze the above depolymerization reaction. Compared with other ionic liquid catalysts, the two ionic liquid catalysts [Emim][Ac] and [Bmim][Ac] have extremely high catalytic performance in catalyzing the depolymerization and upgrading of polyester to carboxylic acid ester and boric acid ester.

[0061] Comparative Example 6

[0062] In this comparative example, in order to further demonstrate the performance difference between the ionic liquid catalyst (taking [Emim][Ac] as an example) of the present invention and other non-ionic liquid catalysts in catalyzing the depolymerization and upgrading of polyester to carboxylic acid ester and boric acid ester, different catalyst types and amounts were set while keeping other parameters unchanged to measure the respective reaction results.

[0063] Test group 1 (reacted for 1 hour at the optimal dosage of hydrotalcite, the weight of hydrotalcite relative to the mass of 0.192g PET was about 15.6wt%): 0.192g CR purity PET powder (1mmol), 0.136g p-methylphenylboric acid (1mmol), 0.03g Mg4-Al1-LDO and 4mL methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple and a programmable temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 93%, and the yield of p-methylphenylboric acid was 90%.

[0064] Test group 2 (hydrotalcite and ionic liquid catalyst reacted for 1 hour under the same gram conditions, and the gram of hydrotalcite accounted for about 5wt% of the mass of 0.192g PET)

[0065] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of CR-pure PET powder (1 mmol), 0.136 g of p-methylphenylboric acid (1 mmol), 0.01 g of Mg4-Al1-LDO, and 4 mL of methanol were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1 hour. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 84%, and the yield of p-methylphenylboric acid was 86%.

[0066] Test group 3 (ionic liquid catalyst and hydrotalcite reacted for 1 hour under the same gram conditions, and the mass proportion of ionic liquid catalyst relative to 0.192g PET was about 5wt%): 0.192g CR purity PET powder (1mmol), 0.136g p-methylphenylboric acid (1mmol), 0.01g [Emim][Ac] and 4mL methanol were added to an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller. After placing the autoclave reactor, stirring and heating were turned on. The reaction system was heated to 180°C and reacted at this temperature for 1h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The yield of dimethyl terephthalate was 99%, and the yield of p-methylphenyl borate was 91%.

[0067] Comparing the above three experiments, it can be seen that the ionic liquid catalyst [Emim][Ac] can greatly improve the performance of PET depolymerization and upgrading to dimethyl terephthalate and p-methylphenyl borate compared with hydrotalcite. The PET decomposition rate under the catalysis of [Emim][Ac] can basically reach 100%, which is much higher than that of the hydrotalcite catalyst.

[0068] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for upgrading polyester depolymerization to carboxylate and borate by catalyzing ionic liquid, characterized in that: include: S1. Put crushed polyester materials, boric acid raw materials, ionic liquid catalysts and methanol solvents into a reaction kettle to form a reaction system; wherein the polyester material is polyethylene terephthalate, polypropylene carbonate, polyethylene adipate or polyethylene succinate; the boric acid raw material is aryl boronic acid or phenylboronic anhydride, and the aryl boronic acid is p-methylphenylboronic acid, 4-methoxyphenylboronic acid or 4-fluorophenylboronic acid; the ionic liquid catalyst is imidazole-type ionic liquid [Emim][Ac] or [Bmim][Ac], and the structural formula is as follows: S2, placing the reactor containing the reaction system at a depolymerization temperature of 160-200° C. for 30-60 min of depolymerization reaction, and cooling to room temperature after the reaction is completed to obtain a depolymerization product containing dicarboxylic acid ester and aryl borate ester.

2. The method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid according to claim 1, characterized in that: In the reaction system, the added amount of the boric acid raw material is the same as the molar amount of the polyester material.

3. The method for upgrading polyester depolymerization to carboxylate and borate by ionic liquid catalysis according to claim 1, characterized in that: In the reaction system, the added amount of the ionic liquid catalyst is 3-10 mol% of the polyester material.

4. The method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid according to claim 1, characterized in that: In the reaction system, the added amount of the ionic liquid catalyst is 5 mol% of the polyester material.

5. The method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid according to claim 1, characterized in that: In the reaction system, the added amount of the methanol solvent is 3-6 mL / mmol of the polyester material.

6. The method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid according to claim 1, characterized in that: The polyester material is waste of polyethylene terephthalate.

7. The method for upgrading polyester to carboxylic acid ester and boric acid ester by ionic liquid catalysis as claimed in claim 6, characterized in that: The waste is in the form of discarded bottles made of polyethylene terephthalate, discarded matrix films, and colored bundling ropes.

8. The method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid as claimed in claim 7, characterized in that: The waste must be crushed into centimeter-sized flakes, particles or powders before being added to the reactor.

9. The method for upgrading polyester to carboxylic acid ester and boric acid ester by ionic liquid catalysis as claimed in claim 1, characterized in that: The ionic liquid catalyst is [Emim][Ac].

10. The method for upgrading polyester depolymerization to carboxylic acid ester and boric acid ester by catalyzing ionic liquid according to claim 1, characterized in that: The depolymerization temperature is 180°C.

Citation Information

Patent Citations

  • Boric acid ester synthesis method

    CN101735254A

  • Method for alcoholysis recovery of waste PET polyester by using ionic liquid as catalyst

    CN116283566A

  • Depolymerization of polymers with ester, ether and carbonate linkages using acidic ionic liquid (AIL) catalyst

    WO2021171311A1